General practice attendances among patients attending a post- COVID-19 clinic: a pilot study. Issue 3 (June 2021) - Broughan, John; McCombe, Geoff; Avramovic, Gordana; Crowley, Des; Downey, Cheyenne; O'Sullivan, Joanne Downey; Fawsitt, Ronan; McHugh, Tina; O'Connor, Eileen; Perrotta, Carla; Cotter, Aoife G; Lambert, John S; et al.
No abstract available